Brincalidade: ativando metamorfoses de transformação vital no tempo da besteira - Rios, Livia Sernache (2023)
This thesis has as its purpose develop a playability proposal in a communicational context that aims relations concerning body and environment. As a parallel goal, it intends to define differences game and play. The object is engagement and reciprocity movements that are body produces when people meet and play. Its proposal is to illuminate playability multispecies movements, to create conditions for life blooming, activating metamorphosis. It comprehends as playability movements investigative and inventive relations that impels living. These movements build cocoons, in which rebirths emerges as possibilities, with playing and working as tools to intensify life, making it continuing. The proposal of playability has continuity as a principle and grasp as its main dynamics. It states that playing stimulates a powerful intention of not restraining one only to survive, but to exist creating furtive ludic strategies. Among ant living social rules, the hypothesis is that illuminating playability movements can help us to be really here to cope with problems that need answers. This research originates from bibliographical reviews and attention to playability movements able to create worlds apart in everyday life. The theoretical foundation comes from and dialogues with the academicals field of the ludic theories (Brian Sutton-Smith, Stuart Brown, Peter K. Smith, Anthony Pellegrini), at the same time it considers playing under evolutive perspectives (Gordon Burghardt, Marc Bekoff, Robert Fagen), as well as the Animal Studies (Donna Haraway, Vinciane Despret, Juliana Fausto). And, to think about the body-environment relation, this study is based, especially, in the Bodymedia Theory (Katz and Greiner), conscious that what are under discussion are our adaptation inventive abilities. In times like ours, if we understand ourselves as human potential generators, path creators and managers of new rules and shapes, we can empower the necessary changings. That represents an invitation to question: is there, really, a playability movement?